DEVELOPMENT OF METHODOLOGIES FOR THE MASS BREEDING OF Typhlodromalus tenuiscutus McMurtry & Moraes (Acari: Phytoseiidae) IN YUCCA - MESA-C., NORA CRISTINA; LENIS-C., JORGE IVÁN; BRAUNI, ANN; DUQUE, MYRIAM CRISTINA (Revista Colombiana de Entomología, 1993)
To develop methods for massive production of Phytoseiidae mites with the aim to get an induced regulation of tetranychid mites, it is necessary to know some basic aspects related with the increasing capability of the beneficial mite, the prey disponibility on the provided foliage and the natural environment where the predator will be released. The purpose of this research was to choose a technique for maximum production of Phytoseiids populations per rearing unit in the less possible time and under conditions resembling the cassava crop. Five systems were tested: The first one called "natural" which consists in plants placed in the field and protected with a roofed cage was 900 females where released; and Tour methods called "artificials" designated as Stratified fruitier, Mesa & Bellotti, Modified Dutch, and Plastic bowl, were infested with 100 females/each at the beginning of the assay. The experiment was conducted in the cassava fields in shadowy and outdoor sites, at CIAT-Palmira. Leaves collected from the field and from screen houses were used as a rearing substrate. It was possible to verify in the cassava plants that besides the establishment of the initial population, a 96.6% increment in the T. tenuiscutus population occurred in the upper and medium thirds of the plants, 15 days after the released. The artificial methods were evaluated 7 days after infestation and it was confirmed that in both, the shadowy and the outdoor environments is possible to establish successfully the rearing as well as to increase significantly the mite population in any of the rearing units, using the foliage produced in the screen houses.